Impact of the halitosis on QoL in overweight and obese patients: Based on six years of experience in two centers in sulaimani governorate, Kurdistan Region/Iraq, and case series study - Ahmed, Hiwa Omer; Zmnako, Sherko Saeed F.; Amin, Zanyar Mustafa; Ezzat, Rajan Fuad; Kakarash, Aram; Omer, Shahen H.; Othman, Hawbash; Sherif, Bawan (Annals of medicine and surgery, 2019)
The patients who are overweight and obese, are under stress of excess body weight, embarrassed, one may imagine the impact of halitosis on this group of patients, this is an attempt to evaluate this extra impact, and which aspect of quality of life will be affect in the overweight and obese. A prospective case series study including 885 overweight or obese patients, they were consulting for advice, diet and or drugs and various bariatric operations. A group of normal weight patients with halitosis, matched in age group and gender were enrolled as a control group for comparison. Patients who have either oral causes of the condition or pseudo halitosis or halite-phobia or were using drugs like phenytoin, cyclosporine or calcium channel blockers, isosorbide di-nitrate, Chloral hydrate, Nitrites and Nitrates, Dimethyl sulphoxide, Disulphiram, cytotoxic agents, Phenothiazine were excluded. The work conducted over a period of 6 years from February 1st, 2012 to March 1st, 2018. Prospective evaluation of the type and etiology of halitosis was done by using organoleptic measurement, which is not a slandered but evaluated by a group of academic colleagues. The patients were advised to avoid eating odiferous foods for 48 hours before the assessment and both the patient and the examiner should refrain from drinking coffee, tea or juice, smoking and using scented cosmetics before the assessment. Halitosis in the overweight and obese patients magnifies the negative aspects of quality of life: avoidance, narrow social circle (P Value = 0.3415, 95% confidence interval = 11.43924–29.67085), avoidance of sex by partner (P Value = 0.0143, 95% confidence interval = 04.11537–17.08480), low self-esteem (P Value = 0.0100, 95% confidence interval = 10.66794–28.44776), teasing by others and negative thoughts (P Value = 0.4013, 95% confidence interval = 11.43924–29.67085). While obesity was not a cause of avoidance of to be kissed by partner in obese patients, but was a direct cause for this avoidance in obese patients with halitosis (P Value = 0.0143, 95% confidence interval = 04.11537–17.08480). Halitosis in normal weight patients affects the quality of life remarkably but not to the extent of halitosis in overweight and obese patients, especially social life and self-esteem which will suffer most. The quality of life of overweight and obese, especially emotional and social aspects was significantly disturbed by halitosis more than normal weight subjects with halitosis. •Halitosis is a common problem in general population.•There is a relation of overweight and obesity with some oral conditions causing halitosis.•The patients who are overweight and obese, are under stress of excess body weight.•One may imagine the impact of halitosis on patients who are overweight and obese.•Halitosis in the overweight and obese patients magnifies the negative aspects of quality of life.